2016
DOI: 10.1007/s10508-016-0840-1
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Transgender Attitudes and Beliefs Scale

Abstract: TABS represents an addition to the literature in its ability to capture a more nuanced conceptualization of transgender attitude not found in previous scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 28 publications
2
87
0
3
Order By: Relevance
“…In their study they found that 60% of the respondents reported being victims of harassment by strangers on the street, verbal abuse, assault with a weapon and/or sexual assault. More than one-third (37%) of respondents also reported being disciplined at work, being degraded or treated unfairly, being fired and, consequently, experiencing economic problems (Hill and Willoughby, 2005).…”
Section: Transphobic Attitudes In Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study they found that 60% of the respondents reported being victims of harassment by strangers on the street, verbal abuse, assault with a weapon and/or sexual assault. More than one-third (37%) of respondents also reported being disciplined at work, being degraded or treated unfairly, being fired and, consequently, experiencing economic problems (Hill and Willoughby, 2005).…”
Section: Transphobic Attitudes In Generalmentioning
confidence: 99%
“…Transgender people can be subject to severe violence though virtually all are subject to significant and harmful microaggressions and transphobic prejudice (Grant et al, 2011). Transphobia refers to negative beliefs and attitudes about transgender people, including aversion and irrational fear of masculine women, feminine men, transvestites, transgender, or transsexuals (Hill and Willoughby, 2005). The transgender group has historically been a marginalized group, and although today transgender people are more accepted by society, many health and mental health professionals (physicians, psychologists, social educators) either do not have knowledge or positive attitudes and do not believe that they are qualified to provide care services to transgender people and therefore avoid doing so Cornelius-White, 2016, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Central to effective clinical practice is the need for comprehensive assessments that informs appropriate treatments, interventions and supports. Practitioners need to be self-aware regarding their own attitudes and values to ensure they actively provide care and support that is affirmative, that is non-judgmental, respectful and inclusive (Fredriksen-Goldsen et al, 2014;Whitman & Bidell 2014;Kanamori et al, 2017). As an integral part of the provision of care and support, mental health practitioners are in an ideal place to create an environment where trans* people can safely disclose, explore and discuss their concerns, aspirations and hopes.…”
Section: Practice Implicationsmentioning
confidence: 99%
“…Despite female medical graduates comprising more than 40% of those successful, the composition of directorships of medical board presents a markedly lower percentage of women [4], with similar trends among other academic medical associations [5], in spite of attempts to understand gender-related attitudes [6]. Nevertheless, both public and corporate administrations require the benefits of attribute-multiplicity that female leadership may endower [7], which implies that obstacles hindering female leadership recruitment as well as those reducing motivation to apply need to be addressed [8][9][10].…”
Section: Introductionmentioning
confidence: 91%